Acceptance model of electronic medical record - Mohd, Haslina; Syed Mohamad, Sharifah Mastura (Faculty of Information Technology Universiti Utara Malaysia, 2005)
This paper discusses acceptance issues of Electronic Medical Record System (EMR), particularly in Malaysia. A detailed overview of EMR and its benefits are firstly discussed. A number of acceptance models are scrutinized. Then factors affecting EMR acceptance are put forward. Finally, before proposing an EMR acceptance model, an instrument formed by adapting and then finding its factors loading is presented.